Attitudes towards polypharmacy and medication withdrawal among older inpatients in Italy. - Galazzi, Alessandro; Lusignani, Maura; Chiarelli, Maria; Mannucci, Pier; Franchi, Carlotta; Tettamanti, Mauro; Reeve, Emily; Nobili, Alessandro; Chiarelli, Maria Teresa; Mannucci, Pier Mannuccio (International Journal of Clinical Pharmacy, 2016)
Background: From 20 to 65 % of older adults receiving polypharmacy take at least one potentially inappropriate medication (PIM), leading to a high risk of adverse drug reactions. The term deprescribing was coined to describe a process of optimization of drug regimens through the withdrawal of PIMs. There is a paucity of evidence on the attitudes, beliefs and willingness of hospitalized patients towards deprescribing.Objective: To measure at hospital discharge inpatients' attitudes and beliefs towards polypharmacy and the potential withdrawal of one or more of their medications using the PATD (Patients' Attitudes Towards Deprescribing) questionnaire and determine if they are associated with participant characteristics.Setting: Geriatric and internal medicine wards in an Italian teaching hospital.Method: Administration of the PATD questionnaire (developed and validated in an Australian outpatient setting, translated and adapted to the Italian setting for this study) to a consecutive sample of 100 older (aged ≥65 years) inpatients with polypharmacy who were interviewed by a nurse or pharmacist at the time of hospital discharge.Main Outcome Measure: Older patients' attitudes and beliefs towards reducing medications and participant characteristics.Results: Eighty-nine percent of patients surveyed would like to reduce the number of daily medications. The desire for deprescribing was not associated with age, sex or number of medications or medical conditions; older patients were less aware of the reasons for taking medications.Conclusion: The majority of hospitalized older adults with polypharmacy think they are taking a lot of drugs and would like to reduce this number. Older adults should not be considered a major limitation on deprescribing interventions. Future research should examine this issue with qualitative studies in order to gain a more in-depth understanding and explore how these findings can be translated into a multidisciplinary deprescribing process.